2005
DOI: 10.1111/j.1439-0450.2004.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Beef Bull Semen Reduced the Risk of Abortion inNeospora‐seropositive Dairy Cows

Abstract: There is an evidence that the epidemiology of neosporosis differs in dairy and beef cattle, such that beef cattle carry a lower risk of abortion. The aim of the present study was to establish whether artificial insemination using semen from beef bulls could reduce the risk of abortion in dairy cows seropositive for the Neospora caninum parasite. Our study was based on yearly serological screening for neosporosis and on the confirmation of Neospora infection in aborted fetuses in two high-producing dairy herds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 39 publications
6
35
1
1
Order By: Relevance
“…The abortion risk increases with increasing levels of N. caninum-specific antibodies in individual animals (239,285,293,360,393,394,423,464,488). De Meerschman et al (113) found a strong association between the level of antibodies in the dam and the occurrence of histopathological lesions in aborted fetuses consistent with N. caninum infection.…”
Section: Abortion Riskmentioning
confidence: 97%
See 1 more Smart Citation
“…The abortion risk increases with increasing levels of N. caninum-specific antibodies in individual animals (239,285,293,360,393,394,423,464,488). De Meerschman et al (113) found a strong association between the level of antibodies in the dam and the occurrence of histopathological lesions in aborted fetuses consistent with N. caninum infection.…”
Section: Abortion Riskmentioning
confidence: 97%
“…N. caninum infection was not demonstrable in any of 70 fetuses or calves born to seronegative cows that received embryos from seropositive donors, whereas 5 of 6 calves resulting from embryo transfer from seronegative donors to seropositive recipients were infected with N. caninum (25 (ii) Artificial insemination of seropositive dams with semen from beef bulls. The results of a study conducted in Spain on two high-producing dairy farms with a mean seroprevalence of 28% suggested that the use of beef bull semen could reduce the risk of abortion in dairy cows on those farms and proposed that this effect might be due to the favorable effect of crossbreed pregnancies on placental function (285).…”
Section: Control Measuresmentioning
confidence: 99%
“…A suggested variant of this strategy is to inseminate all seropositive dams using beef semen, and it has even been suggested that hybrid pregnancies are less susceptible to abortion. 61 A second but similar approach is to perform serology on all potential replacement heifers, regardless of the serologic status of their dams, and then retain only seronegative animals to enter the breeding herd; this serology could be performed from precolostral blood specimens obtained at birth, but more commonly, it would be performed after maternal immunity has waned, perhaps at 6 months of age.…”
Section: Control Optionsmentioning
confidence: 99%
“…Several studies have linked high antibody titers against the parasite to an increased risk of abortion Brickell et al, 2010;Kashiwazaki et al, 2004;López-Gatius et al, 2005;Yániz et al, 2010). Therefore, it seems that cows aborting due to neosporosis have a higher Neospora-specific antibody response than infected but non-aborting cows.…”
Section: Antibody Titration As a Marker Of Abortion Riskmentioning
confidence: 96%